RELIGIOUS MODERATION : Epistemological Perspective - Mahmud, Moh. Natsir (Jurnal Diskursus Islam, 2022)
This article examines religious moderation from an epistemological perspective. One thing that needs to be studied in religious moderation is to properly recognize the doctrine of religious beliefs, sects or specific religious groups to formulate the system of communication and cooperation. Islam has a solid foundation in embodying religious moderation both from the Quran, hadith, the experience of the Prophet Muhammad, and the system of government that existed in history. Religious moderation is a demand that must be embodied in a safe and harmonious community, nation, and state among individuals and social groups. Systematic and planned steps are needed to embody religious tolerance by effectively using the available facilities. The operational pattern of religious moderation has alternative offers with habitus and arena patterns, supported by thorough research. The arena was used to identify the approach method.